2021
DOI: 10.1016/j.tracli.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Bioethical perspective of convalescent plasma therapy for COVID-19: A systematic review

Abstract: Convalescent plasma therapy (CP) has long been used to prevent and treat various infectious diseases before COVID-19 such as SARS, MERS, and H1N1. Because the viral and clinical characteristics of COVID-19 share the similarities between SARS and MERS, CP treatment could be a promising treatment option to save COVID-19. With only low quality medical evidence, but massive media support and a very significant public demand for the use of convalescent plasma for COVID-19, we are now faced with an ethical dilemma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Furthermore, elective major orthopaedic surgeries, such as hip replacement surgery or proximal femur surgery, require an adequate blood supply [ 30 ]. On the other hand, the need for blood during the pandemic has significantly increased, especially the demand for convalescent plasma [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, elective major orthopaedic surgeries, such as hip replacement surgery or proximal femur surgery, require an adequate blood supply [ 30 ]. On the other hand, the need for blood during the pandemic has significantly increased, especially the demand for convalescent plasma [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram is reported in Figure 1 . After the full texts were scrutinized against the inclusion and exclusion criteria, 29 SRs were included in the umbrella review [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and 23 SRs were excluded [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%
“…After the full texts were scrutinized against the inclusion and exclusion criteria, 29 SRs were included in the umbrella review [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and 23 SRs were excluded [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Reasons for exclusion were: SRs not covering or with no informative data on CP therapy...…”
Section: Resultsmentioning
confidence: 99%
“…5,18,43 It proved to decrease the viral load, cytokine response, and mortality rate. 44,45,46 CPT involves collection of plasma from the recovered patients via apheresis and transfused to symptomatic patients, assuming the donor has developed antibodies against the causal agent of the disease. 47,48 During apheresis, neutralizing antibodies (NAbs) and other proteins such as clotting factors, anti-inflammatory cytokines, defensins, pentraxins, natural antibodies, and other undefined proteins are collected from donors.…”
Section: Mechanism Of Actionmentioning
confidence: 99%